Navigating transnational reading of Abdulrazak Gurnah's text as a getaway to challenge nationalism - Alam, Umma Maimuna (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2023.